Exploring the Inclusive Classroom Practice in a Public Junior School in Malang: A Case Study - Diva Izzatul Islami; Feriza Dwimas Amaldi; Agnes Wahidah Salsabilla; Alvina Alda Salsabilla; Lestari Setyowati (Penerbit STKIP PGRI Bangkalan, 2025)
This study explores the practice of Inclusive Education in EFL context, especially in English teaching practices in the classrooms, along with the challenges, and solutions provided at one of public junior high schools in Malang, East Java, Indonesia, by showing how students with special education needs are supported. In this qualitative case study research, the tools used in data collection are semi-structured interviews and classroom observations concerning English teachers and students with SEN. The findings point out that the school accommodates SEN students by means of differentiated teaching, special materials, and adapted assessments. Yet, several challenges persist in the areas of lack of infrastructure, inadequate teacher training, and problems in classroom management. The research also encourages some practical solutions, for example, the formation of collaborative teams of teachers and better communication with parents. This study contributes to the insights of inclusive practices in EFL settings with recommendations on how teacher preparedness and resource allocation need to be improved to foster equitable learning environments.